Hippocampal control of repetition effects for associative stimuli. Issue 7 (18th April 2014) - Kremers, Nico A.W.; Deuker, Lorena; Kranz, Thorsten A.; Oehrn, Carina; Fell, Juergen; Axmacher, Nikolai
ABSTRACT Recent findings suggest that repetition effects interact with episodic memory processes that are putatively supported by the hippocampus. Thus, the formation or refinement of episodic memories may be related to a modulating signal from the hippocampus to the neocortex which leads to sparser or more extended stimulus representations (repetition suppression or enhancement), depending on the type of stimulus and the brain site. This framework suggests that hippocampal activity during the initial presentation of a stimulus correlates with the magnitude of repetition effects. Here, we tested this hypothesis in an fMRI study in which associations between faces and buildings were presented twice. BOLD responses showed repetition suppression in fusiform face area (FFA) and parahippocampal place area (PPA), most likely due to a refinement of existing category representations. Hippocampal activity during the first presentations was correlated with the amount of repetition suppression, in particular in the FFA. Repetition enhancement effects were observed on BOLD responses in posterior parietal cortex, possibly related to the formation of new representations of associative stimuli. The magnitude of parietal BOLD repetition effects depended on successful memory formation. These findings suggest that both repetition enhancement and repetition suppression effects are influenced by a modulating signal from the hippocampus. © 2014 Wiley Periodicals, Inc.